Current Management of Amblyopia with New Technologies for Binocular Treatment - Boniquet-Sanchez, Sandra (Vision (Basel), 2021)
Amblyopia is the most common cause of monocular poor vision affecting up to 3.7% of the global population. Classically, the first step in treatment has been optical correction, followed by patching and/or pharmacological treatment. However, this is an evolving scenario, since researchers and clinicians are interested in new binocular treatments due to the increasing development of new technologies. In this article main, current binocular treatments as Dig Rush, falling blocks, I-BiT, Occlu-tab, Vivid Vision, and movies are reviewed for binocular amblyopia management.